The role of the court to protect the rights of man and citizen (Journal of actual problems of jurisprudence, 2018)
This article discusses that before the courts of the Republic of Kazakhstan faces challenges that provide protection guaranteed by the Constitution of Kazakhstan personal rights and freedoms, socio-economic and political rights of man and citizen. The activities of the court to protect the rights referred to justice, while the activities of other bodies such as the protection of justice is not. The judiciary has a pronounced character of law enforcement, resulting in a form of judicial protection of the rights and legitimate interests of the most extensive and thoroughly regulated.Key words: court, the judiciary, the protection of the judicial power.